Transparent, eco-friendly, super-tough "living" supramolecular polymers with fast room-temperature self-healability and reprocessability under visible light. (2nd March 2020) - Fan, Wuhou; Jin, Yong; Shi, Liangjie; Du, Weining; Zhou, Rong
Abstract: Herein, combining the visible light-induced dynamic diselenide bonds and pendant 2-ureido-4[ 1H ]-pyrimidinone (UPy) groups, a novel type of eco-friendly water-dispersed supramolecular polymers (DSe-WSPs) with excellent healing properties was developed. Transparent films obtained from DSe-WSPs emulsions demonstrated improved mechanical properties after the incorporation of UPy groups. Synergy effect of dynamic diselenide bonds and UPy groups was crucial for the fast healing process (10 minites) of DSe-WSPs polymers under visible light with a healing efficiency over 95.0%. Through this elaborated architecture, a fast room temperature self-healability and reprocessability could be achieved in super-tough polymers (69.10 MJ m −3 ) with eco-friendly feature, which has not been realized in the reported self-healing polymers. To our exiting, the DSe-WSPs polymer can be also used as a macro-initiator to initiate polymerization of vinyl monomer under visible light, which was firstly reported for self-healing polymers. These characteristics of fast room temperature self-healability, reprocessability, photo-initiated polymerization ability, and eco-friendly feature with robust mechanical properties present a feasible way to satisfy the demands of high performances and sustainability for the next-generation materials. Graphical abstract: Image 1 Highlights: Eco-friendly healable supramolecular polymers containing dynamic Se–Se were prepared. Synergy effect of dynamic Se–Se and UPy groups was crucial for fast healing (10 min). Fast self-healability and robust mechanical properties were achieved simultaneously. Visible light is an easily manipulated way to achieve room-temperature self-healing. Self-healing polymer was firstly used as a macro-initiator to initiate polymerization.